Hubungan Status Anemia, Kadar FE Tablet Tambah Darah dan Kepatuhan Minum Tablet FE Dengan Kejadian Anemia pada Ibu Hamil - Istiningsih, Titik; Meyasa, Lola (Institut Citra Internasional, 2024)
An indicator of the success of a country's health services can be seen from the Maternal Mortality Rate (MMR). The bad effects of anemia in pregnancy for pregnant women include premature births, abortions and congenital defects, thereby increasing maternal and fetal mortality and morbidity. The aim of this research is to determine the prevalence rate of anemia and anemia status in pregnant women who consume blood supplement tablets, determine the iron/Fe levels in blood supplement tablets consumed by pregnant women, and determine the level of compliance with taking medication in pregnant women. This research method uses an analytical observational design, with a cross sectional design. The independent variables are the FE levels in blood supplement tablets and the mother's level of compliance in consuming blood supplement tablets. The results of the relationship between the level of adherence to consuming blood supplement tablets and anemia status are (p=0.000), which shows a significant relationship with the incidence of anemia. The relationship between iron levels and anemia status obtained statistical results with Fe levels ? 60 mg (p=0.000), showing a significant relationship with the incidence of anemia. Based on the relationship between the characteristics of pregnant women and the incidence of anemia in the variable age (p=0.000), Upper Arm Circumference (p=0.000), there is a significant relationship and influences the incidence of anemia. Variables that did not have a significant relationship with the incidence of anemia were parity (p=0280) and education (p=0.640).